Role Of Sonography In Diagnosis Of Acute Abdomen In Various Pathologies And Assesment With Shear Wave Elastography In Patients With Acute Appendicitis In Pediatric Age Group In A Tertiary Care Centre - Pavani, Pavani; Kaliperumal , Kaliperumal; Remya, Remya; M.G , Sai Shankar (Journal of Neonatal Surgery, 2025)
Acute abdominal pain is a prevalent clinical presentation in the pediatric population and accounts for a substantial number of emergency department visits. Diagnosing the exact cause can be complex due to the overlapping symptoms among various pathologies. Acute appendicitis is one of the leading causes of surgical intervention in children, and early diagnosis is crucial to prevent complications such as perforation, abscess formation, and peritonitis. To overcome these limitations, shear wave elastography (SWE) has emerged as a promising adjunct. SWE is a quantitative imaging technique that assesses tissue stiffness by measuring the speed of mechanically generated shear waves. Inflamed tissues typically exhibit increased stiffness compared to their normal counterparts. In the context of appendicitis, this difference can be captured using SWE, potentially providing a more definitive diagnosis. The purpose of this study was to assess the diagnostic utility of combining conventional grayscale ultrasonography with SWE in evaluating acute appendicitis in pediatric patients. Furthermore, we aimed to explore the feasibility of incorporating SWE as a routine part of abdominal sonography protocols in children presenting with acute abdominal symptoms